The relationship between job insecurity, shock, and turnover intention, amongst survivors of organizational downsizing - Ho, J,A.; Sambasivan, M.; Liew, E.Y. (Universiti Putra Malaysia, 2013)
It is often thought that survivors of a downsized organization should be thankful for remaining in their jobs, and that they should respond positively by helping the organization to achieve its goals. However, these individuals often have the intention of leaving the organization. The purpose of this study is to examine the factors that influence the turnover intention of survivors of downsized organizations. We hypothesized that survivors were more likely to think about leaving their organization when they perceived insecurity in their jobs and considered the downsizing decision taken by top management as a "shock." We tested this hypothesis on 187 surviving employees of downsized organizations in Malaysia. The important findings of this study are that the survivors' turnover intention is significantly related to shock, job insecurity, and organizational level. Hence, organization leaders need to plan carefully before implementing their organization's downsizing, as shocks do influence survivors' turnover intention.